Smart-UMKM : Aplikasi Penyedia Business Model Canvas dan Pelatihan Sebagai Wadah dalam Pengembangan UMKM di Indonesia - Erwandi, Joshua Theo; Sidauruk, Selna A.; N, Septiana G.A.; Usli, Vera A. (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2023)
Factors that make it difficult for MSMEs to develop are due to lack of mastery of technology, not making a business plan, lack of marketing and several other factors. Therefore, the author offers an idea, namely Smart-UMKM, where Smart-UMKM provides a business model canvas or business model framework that prospective MSMEs want to create. Not only that, from this framework prospective MSME players will be helped to develop their businesses through Smart-UMKM by providing the required skills training. The Smart-UMKM application with BMC is very appropriate to use so that the MSME sector can develop its business and be able to compete in the market, is effective for start-up businesses, is suitable for online businesses, the value of consumer placement and costs tend to be low because in BMC there are nine (9) elements as the key to running an optimal business